The genus Crocinoboletus (Boletaceae, Boletales): a new species and updated information for previously described species - Wu, Lu-Ling; Liang, Zhi-Qun; Xue, Rou; Fan, Yu-Guang; Jiang, Shuai; Fu, Yong-Qing; Zeng, Nian-Kai; Su, Ming-Sheng (Phytotaxa, 2019)
The morphology, ecology, and phylogenetic relationships of species of Crocinoboletus (Boletaceae, Boletales) were investigated. One species, C. pinetorum, new to science, is characterized by a pileus yellowish orange to pale orange in color, surface of pileus and stipe usually unchanging in color when bruised, shorter basidiospores measuring 9.5–11.5 × 4–5 (–5.5) μm, and its association with pine trees. Information on C. laetissimus and C. rufoaureus is updated. A key to all known taxa of Crocinoboletus is also provided.